2022
DOI: 10.4314/ejhs.v32i4.17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antibiotic resistance and virulence of Enterococcus spp. isolated from traditional cheese types

Abstract: BACKGROUND: Enterococci are naturally found in the gastrointestinal (GI) tract of animals and humans, as well as animal-derived foods and vegetables. We here aimed to determine the prevalence, antibiotic resistance, and virulence determinants of E. faecium and E. faecalis in traditional cheese in the North-west of Iran.MATERIALS AND METHODS: Fifty specimens of popular traditional cheese from dairy stores of Urmia and Tabriz, Iran, were collected. Identification of the genus and species of enterococci was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…Enterococcus faecalis as the predominant species in the tested materials. The present study demonstrated that E. faecalis was the most common in the tested dairy products, which was in agreement with the findings of other studies [ 2 , 9 , 27 , 29 ]. Jahansepas et al even isolated fivefold more E. faecalis (83.33%) than E. faecium (16.67%) from cheese samples in Iran [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Enterococcus faecalis as the predominant species in the tested materials. The present study demonstrated that E. faecalis was the most common in the tested dairy products, which was in agreement with the findings of other studies [ 2 , 9 , 27 , 29 ]. Jahansepas et al even isolated fivefold more E. faecalis (83.33%) than E. faecium (16.67%) from cheese samples in Iran [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…The present study demonstrated that E. faecalis was the most common in the tested dairy products, which was in agreement with the findings of other studies [ 2 , 9 , 27 , 29 ]. Jahansepas et al even isolated fivefold more E. faecalis (83.33%) than E. faecium (16.67%) from cheese samples in Iran [ 27 ]. However, one report stated a higher frequency of E. faecium than E. faecalis in Serbian cheeses [ 30 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations